THE STUDENTS’ OBSTACLE ON SYNCHRONOUS LMS– ONLINE ENGLISH LEARNING DURING PANDEMIC - Marselina Yolanda Intan Larasati (ETERNAL (English Teaching Journal), 2022)
In this pandemic, learning materials in 21st-century education are the main obstacles to improving students' quality. The government program followed up that schools were encouraged to hold online classes. The new situation poses several online learning challenges that do not always provide excitement for students when they have to adjust to the pace of learning. Online learning facilitates interaction between teachers and students to conduct language learning in real-time and interactively through online digital platforms such as video, voice calls, and communication via WhatsApp to deliver the material. In addition, speaking and learning strategies on study English as a foreign language for students to actively participate in class. Therefore, the expectations of both students and teachers regarding whether online synchronous classes are effectively implemented or not have not been sufficiently fulfilled. The researcher seeks to investigate the possible challenges in synchronous-online English learning according to students' perceptions. Researchers conducted a survey using observations, questionnaires, and interviews to collect data. Several participants were interviewed on students. The challenge consists of three major problems: technical challenges, situational challenges, and language anxiety. During the home learning strategies program, students revealed that they had different abilities to take online courses simultaneously due to their background and previous experience. However, most students have a desire to maintain strategies to improve their online learning strategies performance and to cope with changing situations. Similarly, the three grand strategies for dealing with their challenges include self-control, external control, and academic strategies. In addition, most students prefer to have asynchronous online classes over synchronous classes because of their flexibility.